Study of vasodilation processes - Sirman, Ya. V.; Savytskyi, I. V. (Journal of Education, Health and Sport, 2019)
To date, the key role of endothelial dysfunction in the occurrence and progression of diabetes mellitus and diabetic retinopathy has been proven. The study was performed on white Wistar rats weighing 180-200 g. According to the tasks, the animals were divided into 7 groups. Our results indicate a violation of vasodilation on the 30th day of experimental diabetic retinopathy with subsequent progression of pathological changes on the 60th and 180th day of the study, as evidenced by a decrease in the content of S-nitrosothiols in group 2 (p <0,001 ), most pronounced in the 3rd stage. When analyzing the data of group № 3, it was found that the correction of the pathological condition with the help of hypoglycemic agents has some positive effect, but does not allow to significantly adjust the pathological development of reduced vasodilatory potential. The results of the 4th group indicate that the involvement of nitric oxide donor and aflibercept in the correction of diabetic retinopathy corrects the pathological changes and helps to restore the physiological pathway of nitric oxide synthesis and vascular tone, the maximum effect is observed on the 180th day of the experiment, but normative cannot be achieved. It is observed that the correction of the simulated pathological condition by reducing hyperglycemia, administration of aflibercept and bromfenac (group № 5) gives positive results in the first stage, but less pronounced than involvement in the complex correction of L-arginine solution in subsequent stages. It was found that rats in which diabetic retinopathy was simulated with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac (group № 6) have a pronounced tendency to normalize the studied marker of hypoxia in comparison with the previous methods in the second stage. nitrosothiols at the time of reaching the 3rd stage is reduced. The obtained data suggest that the method of correction chosen in group 7 (correction of hyperglycemia, aflibercept, L-arginine and citicoline solution) more pronouncedly normalizes the content of the vasodilation marker compared to other groups of our experiment, which is pronounced in long-term correction - on 180th day.